Avaliação da prática desenvolvida num centro de atenção psicossocial – capsiii do município de Curitiba - Adachi, Flavia Vernizi (2017)
This dissertation proposed to evaluate the practice of Mental Health in the Center for Psychosocial Care - CAPS, a strategic service within the mental health network, using the Community Practices Analysis Model (Voss and Kafrouni, 2014), built on the Theory of Activity From the perspective of Cultural Historical Psychology. First, a model was elaborated from the regulatory documents of the National Mental Health Policy, contemplating how the CAPS should work ideally. After that, we conducted semi-structured interviews with 10 CAPS professionals, 7 users, 1 family member and 3 NASF professionals. Based on the information gathered, it was possible to identify the elements of CAPS mental health practice, based on their concrete reality, systematizing diagrams for each segment, comparing them with the model elaborated from the regulations. The study revealed that although there is a superficial understanding about the practice performed in the service, there are aspects that were distorted or misunderstood by the actors, generating disparity between doing and saying (Nicolini, 2013), causing both relational and procedural damages And leading to the alienation of the consciousness of the agents of practice. It is concluded that the Model of Analysis of Community Practices can be understood as a relevant tool for surveying the diagnosis of practices through the identification of the subjective and symbolic dimension, promoting visibility to aspects not observable in the daily life, allowing processes of critical reflection and activities Transformers.